Promising adoption of an electronic clinical decision support system for antenatal and intrapartum care in rural primary healthcare facilities in sub-Saharan Africa: The QUALMAT experience. Issue 9 (September 2015) - Sukums, Felix; Mensah, Nathan; Mpembeni, Rose; Massawe, Siriel; Duysburgh, Els; Williams, Afua; Kaltschmidt, Jens; Loukanova, Svetla; Haefeli, Walter E.; Blank, Antje
Highlights The QUALMAT eCDSS was successfully implemented in rural African health care sites. The QUALMAT eCDSS was constantly used over 20 months. The health workers perceived it as useful and user-friendly. Crucial facilitators and barriers to implementing such systems were defined.